RENCANA STRATEGIK MANAJEMEN KURIKULUM MERDEKA PADA MADRASAH UNTUK MENINGKATKAN PRESTASI AKADEMIK SISWA MTSN 3 PURWAKARTA (STUDI KASUS DI MTSN 3 PURWAKARTA) - Syuhada, Imam; Umara, Rohmat; Firman Hidayat, Pian; Nurmilah, Irma; Handayani, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the strategic planning of curriculum management in supporting the implementation of the Merdeka Curriculum at MTsN 3 Purwakarta and its impact on improving students' academic achievement. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings show that curriculum planning was carried out collaboratively through the development of operational documents and the formation of achievement-focused classes. The organization of curriculum implementation involved a curriculum development team and teacher capacity strengthening. Learning activities were conducted with differentiated, project-based, and student-centered approaches. Evaluation was carried out regularly through supervision and performance-based assessments. The strategic planning model applied at MTsN 3 Purwakarta has proven effective in enhancing academic quality and can serve as a model for other madrasahs in implementing the Merdeka Curriculum successfully. Keywords: Strategic Planning, Curriculum Management, Merdeka Curriculum, Academic Achievement, Madrasah